2007
DOI: 10.1007/s11255-006-9077-6
|View full text |Cite
|
Sign up to set email alerts
|

Loss of p27(Kip1) CDKI is a predictor of poor recurrence-free and cancer-specific survival in patients with renal cancer

Abstract: The importance of cyclin-dependent kinase inhibitors (CDKI) in benign and malignant urological diseases is a subject of intense ongoing investigation. The goal of the current study was to analyze the expression of p27((Kip1))CDKI in benign and malignant renal cells and assess their possible association with different clinical parameters. Expression of p27((Kip1)) was evaluated and compared in 24 normal human kidneys and in 52 renal cell carcinoma (RCC) tissue samples. Intensity of the expression was compared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…( 22,24 ) Indeed, loss of nuclear p27 Kip1 has been linked with renal tumorigenesis and has been shown to be associated with increasing tumor grade and to be a risk factor for disease recurrence and cancer‐related death in RCC patients. ( 7,26,27 ) Regardless of the underlying molecular mechanisms, our findings confirmed that loss of nuclear p27 Kip1 is a frequent event in RCC and is related to tumor grade as well as to the clinical outcome of patients both in terms of DFS and OS (Fig. 2a,b).…”
Section: Discussionsupporting
confidence: 77%
“…( 22,24 ) Indeed, loss of nuclear p27 Kip1 has been linked with renal tumorigenesis and has been shown to be associated with increasing tumor grade and to be a risk factor for disease recurrence and cancer‐related death in RCC patients. ( 7,26,27 ) Regardless of the underlying molecular mechanisms, our findings confirmed that loss of nuclear p27 Kip1 is a frequent event in RCC and is related to tumor grade as well as to the clinical outcome of patients both in terms of DFS and OS (Fig. 2a,b).…”
Section: Discussionsupporting
confidence: 77%
“…Given the established significance of c-myc in renal cancers (2023), our demonstration of c-myc as a direct downstream target gene of CoAA is intriguing and substantiates the potential significance of CoAA in renal cancers. Moreover, our data suggest that the skp2 -p27/Kip1 axis, another downstream target of CoAA, has physiological and clinical relevance to renal cancers (24, 25) (Figure 6D). Since CoAM can antagonize the cellular functions of CoAA, our results suggest that regulating the ratio of CoAA versus CoAM isoforms could be a pivotal strategy to influence cellular physiologies.…”
Section: Discussionmentioning
confidence: 72%
“…Expression of CDKN1B is significantly decreased in renal cell carcinoma (RCC) as compared with normal kidney tissue. Loss of CDKN1B expression is a risk factor for disease recurrence and the strongest predictor of cancer-specific survival [92]. …”
Section: Clinical Implication Of Cell Cycle Dysregulationmentioning
confidence: 99%